Electrochemical Investigation of Adsorption of Single‐Wall Carbon Nanotubes at a Liquid/Liquid Interface. Issue 1 (13th December 2016) - Rabiu, Aminu K.; Toth, Peter S.; Rodgers, Andrew N. J.; Dryfe, Robert A. W.
Abstract: There is much interest in understanding the interfacial properties of carbon nanotubes, particularly at water/oil interfaces. Here, the adsorption of single‐wall carbon nanotubes (SWCNTs) at the water/1, 2‐dichloroethane (DCE) interface, and the subsequent investigation of the influence of the adsorbed nanotube layer on interfacial ion transfer, is studied by using the voltammetric transfer of tetramethylammonium (TMA + ) and hexafluorophosphate (PF6 − ) as probe ions. The presence of the interfacial SWCNT layer significantly suppresses the transfer of both ions across the interface, with a greater degree of selectivity towards the PF6 − ion. This effect was attributed both to the partial blocking of the interface by the SWCNTs and to the potential dependant adsorption of background electrolyte ions on the surface of the SWCNTs, as confirmed by X‐ray photoelectron spectroscopy, which is caused by an electrostatic interaction between the interfacial SWCNTs and the transferring ion. Abstract : Probing the interfacial layer : Liquid/liquid electrochemistry is applied to investigate the electrical properties of single‐wall carbon nanotubes adsorbed at water/1, 2‐dichloroethane interface. Retardation of ion transfer across the interface by the adsorbed nanotube layer shows charge‐based selectivity.